Reversal of handedness of ionic liquid-based chiral block copolymers via self-assembly in solution and bulk phase. Issue 13 (15th March 2022) - Puneet, Puhup; Kumar, Labeesh; Singh, Sajan; Horechyy, Andriy; Srivastava, Rajiv K.; Nandan, Bhanu
Abstract : Polymerized ionic liquid-based block copolymer obtained by the functionalization of polystyrene- block -poly(4-vinylpyridine) with chiral auxiliaries demonstrated self-assembled helical nanofibrils with inversion of helical sense. Abstract : Polymerized ionic liquid (PIL)-based ionic chiral block copolymers (BCPs*) were synthesized by functionalization of a poly(4-vinyl pyridine) segment in poly(styrene)- block -poly(4-vinyl pyridine) (PS- b -P4VP) block copolymer. Because of the ease of the ion exchange reaction with the quaternized PIL block, chirality was induced with l -/d -histidine, which acted as chiral auxiliaries, via ion-exchange reaction. Interestingly, the self-assembled helical nanofibrils of BCPs* divulged the reversal of handedness with respect to intrinsic chirality at the molecular level. Remarkably, a similar reversal of handedness was also observed at the quaternary phase. This peculiar behavior of reversal of handedness was correlated to the molecular packing of helical chains according to a cholesteric hard-core model of liquid crystals possessing a large helical pitch to helix diameter ( P / d ) ratio, where P and d denote the helical pitch and helix diameter, respectively.